Strategy for determining hotong (Setaria italica) planting time based on land water balance study on Yamdena Island, Maluku, Indonesia - JEANNE I. NENDISSA; SEMUEL LAIMEHERIWA; ROBBY G. RISAMASU (Smujo International, 2026)
Abstract. Nendissa JI, Laimeheriwa S, Risamasu RG. 2026. Strategy for determining hotong (Setaria italica) planting time based on land water balance study on Yamdena Island, Maluku, Indonesia. Asian J Agric 10 (1): g100167. https://doi.org/10.13057/asianjagric/g100167. Food security in archipelagic regions still faces significant challenges due to limited food distribution, high dependence on seasonal rainfall, and low diversification of local food sources. One potential commodity that can support food independence in the region is hotong (Setaria italica), which is known to have high adaptability to marginal land conditions and limited agricultural inputs. However, hotong productivity on Yamdena Island, Maluku, Indonesia, is still relatively low, mainly due to the lack of determination of planting time that is in accordance with climate dynamics and soil water availability. This study aims to determine the optimal planting period for hotong through a land water balance analysis approach. The data used include rainfall for 30 years (1995-2024), other climate parameters for 15 years (2010-2024), and soil physical properties data, namely field capacity, permanent wilting point, and water holding capacity, plus crop coefficient values. The analysis was carried out by calculating 75% probability rainfall using the rank ordering method, estimating potential evapotranspiration using Cropwat 8.0 software, and integrating all parameters in a land water balance model based on the Thornthwaite and Mather method. Simulation results from 12 planting scenarios indicate that the planting period from December-March to March-June is the safest for hotong cultivation because soil water conditions remain optimal (≥112.5 mm) without deficits. April-July is still possible with small deficits, while May-November is high risk due to large deficits (90-380 mm) and drought during the critical phase. Statistical analysis using one-way ANOVA revealed significant differences in water deficit among planting scenarios (F=58.47, p<0.001), confirming that early rainy season planting significantly reduces water stress. Therefore, planting at the beginning of the rainy season is recommended to maintain productivity, while serving as a scientific basis for developing an adaptive planting calendar for local food development in archipelagic regions.